Domestic and family violence - Healey, Justin (Issues in society (Balmain, N.S.W.), 2014)
Domestic violence refers to acts of violence that occur between people in an intimate relationship in domestic settings; family violence is a broader term referring to violence between family members as well as violence between intimate partners. These violent acts include physical, sexual, emotional and psychological abuse. This book reveals the prevalence and causes of domestic and family violence, and explains ways of dealing with domestic abuse. Domestic violence is more than a crime, it is an abuse of power by someone in a position of trust. Are you safe in your own home? Also includes: w.